Log in to add a comment

Answered:

1. x = 7

2. x = 0

Step by step solution :

Step 1 :

Advertising Skip

Step 2 :

Pulling out like terms :

2.1 Pull out like factors :

x2 - 7x = x • (x - 7)

Equation at the end of step 2 :

x • (x - 7) = 0

Step 3 :

Theory - Roots of a product :

3.1 A product of several terms equals
zero.

When a product of two or
more terms equals zero, then at least one of the terms must be zero.

We shall now solve each
term = 0 separately

In other words, we are
going to solve as many equations as there are terms in the product

Any solution of term = 0
solves product = 0 as well.

Solving a Single Variable Equation :

3.2 Solve : x = 0

Solution is x = 0

Solving a Single Variable Equation :

3.3 Solve : x-7 = 0

Add 7 to both sides of
the equation :

x = 7

@otaku5h

www.tiger-algebra.com/

X(x + 7)

i assumed that x2 + 7x is actually x^2 + 7x, hence the common factor is x.

i assumed that x2 + 7x is actually x^2 + 7x, hence the common factor is x.